Zeugites capillaris (Poaceae: Centothecoideae) nuevo registro para Veracruz - Mejía-Saules, María Teresa; Castillo-Campos, Gonzalo (Instituto de Ecología, A.C., 1992)
Zeugites capillaris (Hitchc.) Swallen is reported for the first time from the State of Veracruz, on the basis of collections from Cerro of Jalcomulco.